Study on Charge-Transfer Exciton Using Solid State Cathodoluminescence Based on MEH-PPV (Poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene]) - HUANG, JIN-ZHAO; LI, SHI-SHUAI; FENG, XIU-PENG; WANG, PEI-JI; ZHANG, ZHONG (Asian Journal of Chemistry, 2010)
In this paper, the solid state cathodoluminescence (SSCL) is applied to investigate the charge-transfer exciton (CTE). The solid state cathodoluminescence is a brand new luminescence mechanism in organicinorganic electroluminescence system and it is characterized by the two emission peak, 405 and 580 nm. After the thickness of emission layer MEH-PPV (poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene]) is decreased to 80 nm from 120 nm and the third emission peak (480 nm) is observed, which is located between the two traditional solid state cathodoluminescence peaks. It is believed that it is from charge transfer exciton emission.